Brand management strategies : luxury and mass markets - D'Arienzo, William (Fairchild Books, An imprint of Bloomsbury Publishing Inc : Bloomsbury, 2016)
" Brand Management Strategies: Luxury and Mass Markets explains how a brand can successfully drive global business development. The text takes an applied approach with supporting examples from current fashion and non-fashion brands. The book provides an introduction to the evolution of branding, next discusses the consumer and business perspectives of branding, and how to create and maintain successful brands. D'Arienzo's approach rests on these three main pillars of branding: We are all in the Consumer Packaged Goods business. We are all in the business of solving problems for consumers rather than selling to them. We are all in a consumer-centric global culture and brands are its universal language. Building from this strategic framework, a unique theme throughout this book is the analyses of luxury brand strategies and how they differ from their mainstream mass market brand counterparts. Matrices and tools in the book have been developed and tested in both the classroom and boardroom. Brand Management Strategies provides students with the tools, techniques, and strategies needed to learn how to effectively establish a brand and build a sustainable business. "--Resumé vydavatele
Terminologický slovník
Keywords: obchodní značky; řízení značky; řízení vztahů se zákazníky; marketing; brand name products; brand management; customer relationship management; příručky; handbooks and manuals